Using Room Temperature Ionic Liquids as Solvents to Probe Structural Effects in Electro-Reduction Processes. Electrochemical Behavior of Mutagenic Disperse Nitroazo Dyes in Room Temperature Ionic Liquids - Boldrin Zanoni, M; Rogers, E; Hardacre, C; Compton, R (2009)
The electrochemical reduction of the disperse azo dyes Red1, Red13 and Orange1 (Or1) was investigated in the RTILs [C4mim][NTf2] and [C4mpyrr][NTf2], and in contrast with their behavior in conventional aprotic solvents, was shown to proceed via a reversible one electron step to form stable radical anion, which is further reduced at more negative potentials to the dianion. In [C4mpyrr][NTf2], cleavage of the N-H bond on the secondary amine was inferred for Orange1, and the ease at which this cleavage occurred is rationalized in terms of acidity of the amine moiety. The ease of reduction was observed to decrease in the order Or1 > Red13 > Red1, and is related to the electron delocalization within the molecule and the electron withdrawing power of the substituents. The dyes were then oxidized, and Red1 and Red13, bearing an aliphatic amine, were oxidized in a reversible one electron step, to generate the radical cations. The presence of a primary aromatic amine in Or1 provokes a positive shift in the potential of the oxidation peak and shows reversible voltammetry only at scan rates above 200 mV s-1. The ease of oxidation decreases in the order Red1 > Red13 > Or1, and is thought to relate to the detected mutagenic activity of the dyes. © 2009 by ESG.